The agrarian reform experiment in Chile: History, impact, and implications - Valdés, Alberto; Foster, William E. (International Food Policy Research Institute, 2014)
This paper presents what is known about the role of agrarian reform and the subsequent counter reform in producing a successful dynamic evolution of Chilean agriculture.